Worship Space Acoustics 3 Decades of Design - Bradley, David T.; Ryherd, Erica E.; Ronsse, Lauren M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
This book takes the reader on a wide-ranging tour through churches, synagogues, mosques, and other worship spaces designed during the past 30 years. The book begins with a series of essays on topics ranging from the soundscape of worship spaces to ecclesiastical design at the turn of the 21st Century. Perspective pieces from an architect, audio designer, music director, and worship space owner are also included. The core of the book presents the acoustical and architectural design of a wide variety of individual worship space venues. Acoustical consulting firms, architects, and worship space designers from across the world contributed their recent innovative works in the area of worship space acoustics. The contributions include detailed renderings and architectural drawings, as well as informative acoustic data graphs and evocative descriptions of the spaces. Filled with beautiful photography and fascinating modern design, this book is a must-read for anyone interested in religious architecture, acoustical design, or musical performance.    Provides detailed acoustic and architectural information for 67 worship space venues from 12 major religions directly from the acousticians who designed the spaces Features contributions from acoustical consulting firms and worship space designers worldwide, with spaces indexed by consulting firm and by geographic location Includes high-resolution photos and renderings, full-page architectural drawing s, scientific data, an overview of acoustic design for worship spaces, and a glossary of common worship space acoustics terminology David T. Bradley, Ph.D. is an associate professor in the Physics + Astronomy Department at Vassar College. Erica E. Ryherd, Ph.D. is an associate professor in the Durham School of Architectural Engineering & Construction at the University of Nebraska - Lincoln. Lauren M. Ronsse, Ph.D. is an assistant professor in theAudio Arts & Acoustics Department at Columbia College Chicago.
Editors' Preface -- Collection of Essays from Key Design Team Members -- Worship Spaces -- Contributed Worship Spaces List -- Map -- Timeline -- Worship Spaces: 100 - 250 seats -- Worship Spaces: 251 - 500 seats -- Worship Spaces: 501 - 750 seats -- Worship Spaces: 751 - 1000 seats -- Worship Spaces: 1001 - 2000 seats -- Worship Spaces: 2001 - 5000+ seats -- Appendices -- A: Acoustic Design of Worship Spaces: An Overview -- B: Glossary -- C: Worship Spaces Indexed by Location -- D: Worship Spaces Indexed by Acoustical Consulting Firm -- E: Notes on Currency, Units, and Scale -- F: References.
Keywords: Acoustical engineering; Interior architecture; Acoustics; Noise control; Architecture; Buildings; Engineering Acoustics; Interior Architecture; Acoustics; Noise Control; Building Types and Functions